(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, open classes conducted by medical educational institutions in all directions, requirements for their implementation, plan, methodology, guidelines for conducting open classes, and the importance of ensuring the quality of education rni and its importance are highlighted. Information about the possibilities, disadvantages and advantages of conducting open classes in the educational system is presented